Inflation expectations spillovers between the United States and euro area - Aleksei Netšunajev; Lars Winkelmann (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2014)
We quantify spillovers of inflation expectations between the United States (US) and Euro Area (EA) based on break-even inflation (BEI) rates. In contrast to previous studies, we model US and EA BEI rates jointly in a structural vector autoregressive (SVAR) model. The SVAR approach allows to identify US and EA specific inflation expectations shocks. By modeling the heteroscedasticity of the data, we are able to test the identifying restrictions of structural shocks and analyze time-varying spillovers. Adjusted for BEI risk premia, our main result suggests that spillovers of inflation expectations increase during times of macroeconomic stress. We document a significant impact of the European sovereign debt crisis on US expectations. The finding contributes to the discussion about a weakening of inflation control by national central banks and speaks in favor of internationally coordinated policy actions, especially during crisis times.
Keywords: E31; F42; E52; 330; International transmissions; break-even inflation; credibility of monetary policy; structural vector autoregressive (SVAR) analysis; identification through heteroskedasticity